STUDY NETNOGRAFI VIRALITAS LAGU MENDUNG TANPO UDAN NDARBOY GENK - Putut Aji Setio Nugroho (2022)
Music content as a means of entertainment for the community. One of the music content that is entertainment for young people is the song Ndar Boy Genk. This study aims to examine the virality of the song Mendung Without Udan which is sung by using a netnographic study. This research was conducted using qualitative research with netnographic methods. Data collection techniques are carried out with documentation from Youtube. The results of this study indicate that the concept of online mass media is used in the song Mendung tanpo udan Ndarboy Genk version of NdarBoy Genk because many parties, both national and international, have created an effect that makes the song Mendung tanpo udan Ndarboy Genk the NdarBoy Genk version go viral. The virality that the song gets is because mass media or social media users always use the song in various activities such as dancing or just singing the song because it is quite delicious and has thick Javanese vibes.